The relationship between peer attachment and delinquent behavior among young offenders - Siti Noor Fazariah Suis @ Mohd Rusdy; Azahar Che Latiff; Razima Hanim Othman; Norhamidah Jarimal @ Safri (Universiti Malaysia Sabah, 2016)
This study examined the relationship between peer attachment and delinquent behavior among young offender in Sabah. A total of 92 young offenders aged 16-21 years old were selected by using purposive sampling method from rehabilitation institutions in Sabah. The revised version of Inventory of Parents and Peers Attachments (Revised-IPPA-R) and the Junger Delinquency Scale were used in this study. The results showed that there is no significant relationship between peer attachment and delinquent behaviour (r=.023, k>0.05). Recommendations are discussed where attachment could be included as a target for intervention.